Still plodding along? The police response to the changing profile of crime in England and Wales - Loveday, Barry (International journal of police science & management, 2017)
This article considers the new demands placed on police forces arising from the dramatic increase in the numbers of cases of fraud and cybercrime. It assesses the ability - or current difficulty - of the police to respond to this development. The article is directed towards a growing requirement for substantial internal police reform that goes well beyond anything contemplated heretofore. The article draws on the recent and important Her Majesty’s Inspectorate of Constabulary (HMIC) PEEL Review of police efficiency, which for the first time, has raised the question of identifying not just police capacity, but also police force capability. It is evident that although police forces can quickly identify capacity (ranks and police numbers), they experience great difficulty in relation to capability. This relates to the police response to the ‘new’ forms of crime that are now replacing traditional acquisitive crime. Recent cases include the 2016 cyber-attack on Tesco Bank in which £2.5 million was stolen from 9,000 bank accounts, and a major cyber-attack in the same year that disrupted internet services across Europe and the USA. The article seeks to identify current police responses to this development and also highlight the real challenge this problem represents. It recognizes the competing demands made on the police, but suggests that fraud and cybercrime now constitute the greatest threat confronting the police service in England and Wales.